Application of finite element method to compare die textures in microforming - Saraf, Parag. (2013)
With the increase demands in miniaturized products, microforming has become increasingly popular due to its economic advantages. However, the well-established bulk forming technology cannot be applied to microforming due to size and frictional effects. Friction tends to increase in microforming. Studies suggest that texturing of die surface reduces friction even without the use of lubricants. With this as the primary focus the project aims to simulate the effects on dry friction with texturing of die surfaces using Finite Element Method. It aims to determine the size independent frictional property so that it can be used in higher scale simulation without modeling the texture.